2014
DOI: 10.15560/10.1.156
|View full text |Cite
|
Sign up to set email alerts
|

New distribution records of the Buff-fronted Owl Aegolius harrisii Cassin, 1849 (Aves: Strigidae) in Peru

Abstract: Abstract:We review the distribution of the Buff-fronted Owl Aegolius harrisii harrisii in Peru, supported by unpublished museum records and new specimens and observations. Compared to previous published records, the distribution and elevation range for the species in Peru are expanded significantly. Based on all records, we deduce that the overall distribution of A. harrisii in Peru is almost continuous, from the northwestern Andes to the eastern southern Andes, between 250 and 2960 m. The northern Peruvian An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…Asimismo, se revisaron listas de libre acceso sobre aves del departamento (Wiley et al 2014, Foss et al 2021. Además, se revisaron los artículos sobre la avifauna, de las áreas protegidas y de nuevos registros de especies de Loreto (Salazar et al 2003, Armacost Junior 2006, Shahuano Tello et al 2008, Lüthi 2011, Álvarez Alonso et al 2012, Bicerra Canayo 2013, García Bravo & Barrio 2014, Díaz-Alván et al 2017, Schmitt et al 2017, Socolar et al 2018, Ugarte & Lavalle Valdivia 2018, Acosta Diaz et al 2019, Moncrieff et al 2019, Fong Rengifo et al 2020, Garcia Solsol et al 2020, Ruiz-Ramos et al 2020, Vásquez-Arévalo et al 2020.…”
Section: Al�tud (M)unclassified
“…Asimismo, se revisaron listas de libre acceso sobre aves del departamento (Wiley et al 2014, Foss et al 2021. Además, se revisaron los artículos sobre la avifauna, de las áreas protegidas y de nuevos registros de especies de Loreto (Salazar et al 2003, Armacost Junior 2006, Shahuano Tello et al 2008, Lüthi 2011, Álvarez Alonso et al 2012, Bicerra Canayo 2013, García Bravo & Barrio 2014, Díaz-Alván et al 2017, Schmitt et al 2017, Socolar et al 2018, Ugarte & Lavalle Valdivia 2018, Acosta Diaz et al 2019, Moncrieff et al 2019, Fong Rengifo et al 2020, Garcia Solsol et al 2020, Ruiz-Ramos et al 2020, Vásquez-Arévalo et al 2020.…”
Section: Al�tud (M)unclassified
“…Juan Ruiz-Esparza, José Percílio Mendonça Costa, Caroline Santos, Daniela Pinheiro Bitencurti Ruiz-Esparza, Raone Beltrão-Mendes & Stephen F. Ferrari Received 10 October 2016;revised 20 January 2017;published 13 March 2017 Buff-fronted Owl Aegolius harrisii is one of 22 species of Strigidae in Brazil (Sick 1997). The species has a circum-Amazon range (Barlow & Cuello 1964, Fjeldså & Krabbe 1990, König et al 1999, Barrionuevo et al 2008, Ubaid et al 2012) and is found from sea level to 3,800 m (Lima & Castro 1994, Bravo & Barrio 2014. In Brazil, isolated records indicate that A. harrisii is distributed throughout most of the east of the country (Kaminski 2009, Santos 2009, Rebelato et al 2011, Ubaid et al 2012, Santos et al 2014.…”
Section: Appendixmentioning
confidence: 99%
“…Since then, additional data have been gathered and new aspects of the natural history of this species, including its vocalizations and habitat preferences, have been described (e.g. Braun et al 2003;Córdoba and Ahumada 2005;Bodrati and Cockle 2006;Ubaid et al 2012;Bravo and Barrio 2014;Ramoni-Perazzi et al 2014;Ruiz-Esparza et al 2017;Penagos et al 2018). Although these studies have provided important insights into the ecological preferences of the species, most of its life history traits remain poorly understood, and the number and size of its populations are probably underestimated (Enríquez 2015;Girão and Albano 2010;Rosa et al 2015).…”
Section: Introductionmentioning
confidence: 99%